Trend of Pesticide Use in Nepal - Ghimire, Kiran; GC, Arun (Journal of the Plant Protection Society, 2018)
This paper has attempted to analyze the trend of pesticide import, formulation and consumption in Nepal. Nepal has diverse agro-ecological conditions and different agro-climatic conditions necessitate varieties of approaches to crop cultivation and crop protection. The average national use of pesticides in Nepal is 396g a.i./ha with the highest use in the vegetable. This review used relevant secondary data, and information. The study found that the fungicides are the major form of pesticides used in Nepal for the pest control and the trend of pesticides consumption is increasing for agricultural purposes. The Nepal Government has signed different international treaties, made rules and regulations and initiated different types of programs to minimize the use of pesticides.